KESEJAJARAN KARAKTER TOKOH DALAM BUKU “ANAK KAMPUNG PALING FENOMENAL” KARYA DR. M. MUFTI MUBAROK - Putra, Agus Darma (LPPM Institut Pendidikan Nusantara Global, 2022)
Character was a person's nature, which refers to a person's personal qualities. The characters in the book “The Most Phenomenal Village Children” are no exception, who have the same characters in this study. The purpose of this study is to find out the form of parallel reality of the characters through the words and behavior of the characters in the book